Macrophage Receptor With Collagenous Structure Polymorphism and Recurrent Respiratory Infections and Wheezing During Infancy: A 5-Years Follow-Up Study - Francesco Savino; Francesco Pellegrino; Valentina Daprà; Cristina Calvi; Carla Alliaudi; Paola Montanari; Ilaria Galliano; Massimiliano Bergallo (Frontiers Media S.A., 2021)
Background: Recurrent wheezing is a common clinical manifestation in childhood, and respiratory syncytial virus infection is a well-known risk factor. However, the genetic background favoring the development of recurrent wheezing is not fully understood. A possible role of macrophage receptor with collagenous gene (MARCO) polymorphism has been recently proposed.Objective: To investigate a correlation between MARCO rs1318645 polymorphisms and susceptibility to recurrent wheezing during childhood.Methods: We prospectively recruited 116 infants, of which 58 with respiratory syncytial virus bronchiolitis and 58 controls hospitalized at Regina Margherita Children's Hospital, Turin, Italy, between November 2014 and April 2015. All subjects were investigated for MARCO rs1318645 polymorphisms in the first period of life. Genotyping of rs1318645 was carried out by TaqMan mismatch amplification mutation assay real-time polymerase chain reaction procedure. Subjects were then enrolled in a 5-year follow-up study to monitor the occurrence of wheezing and respiratory infections.Results: The analysis of MARCO rs1318645 of allelic frequencies shows an increasingly significant risk to develop recurrent infection (p = 0.00065) and recurrent wheezing (p = 0.000084) with a wild-type C allele compared with a G allele. No correlation was found between wheezing and past respiratory syncytial virus infection (p = 0.057) and for a history of atopy in the family (p = 0.859).Conclusion: Our finding showed that subjects with C allelic MARCO rs1318645 polymorphism are at higher risk for recurrent infection and wheezing episodes during the first 5 years of life. Future studies of genetic associations should also consider other types of polymorphisms.